Selective flocculation of coal and shale - Spencer, L. (1984)
The work presented within this thesis describes an investigation into the selective flocculation behaviour of coal/shale slurries using commercially available polyacrylamide polymers. It is considered that selective flocculation may eventually offer a method of recovering the valuable combustibles which are presently discarded. To date, although numerous, mainly laboratory scale, investigations using organic polymers have been conducted on a variety of mineral combinations, little work has been undertaken on coal/shale slurries.